Resilience in Practice: Responding to the Refugee Crisis in Turkey, Jordan, and Lebanon - Anholt, Rosanne (2020)
Little is known about how the idea of ‘resilience’ translates into practice. It has nonetheless emerged as a dominant theme in the governance of crises, such as political instability, armed conflict, terrorism, and large-scale refugee movements. This study draws on interviews with humanitarian and development practitioners in Turkey, Jordan, and Lebanon working under the Regional Refugee and Resilience Plan to explore how resilience is interpreted and translated on the ground. Results suggest that resilience is translated as the economic self-reliance of refugees, and the capacity for crisis management of refugee-hosting states, enacted through ‘localization’ and strengthening the ‘humanitarian-development nexus.’ The prominence of the political and economic context and the power relations between crisis response actors that it generates reveals the limits of what a buzzword like resilience can achieve on the ground. The findings highlight the need for researchers, policymakers, and practitioners to engage in continuous critical reflection on whether the ways in which resilience policies and programmes are implemented actually improve the ability of systems and vulnerable populations to recover from crisis, as well as on the validity of the assumptions and interpretations on which such policies and programmes are built.